IMPLEMENTASI STRATEGI PENDIDIKAN KARAKTER BERBASIS NILAI-NILAI ISLAM PADA SANTRI KELAS VII MTS DI PONDOK PESANTREN HIDAYATULLAH YOGYAKARTA - Joni Iskandar (Hijri, 2025)
The rapid development of the era has a serious impact on the character of the younger generation, such as weak discipline, low motivation for worship, and lack of social responsibility. Islamic boarding schools are present as an alternative solution that emphasizes comprehensive character development. This study aims to examine the implementation of character education strategies based on Islamic values in class VII MTs students at the Hidayatullah Islamic Boarding School in Yogyakarta. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that character education in this Islamic boarding school is implemented systematically through seven main strategies: role models and leadership, purification of the soul (tazkiyah), teaching (ta‘lim), habituation (ta‘wid), monitoring (mutaba‘ah), motivation and threats (targhib wa tarhib), and reward and punishment (tatswib wa mu‘aqabah). These seven strategies are integrated into five aspects of education (wujūh at-tarbiyah) which include aspects of ruhiyyah, tsaqafiyyah, jasadiyyah, qiyadiyyah, and ijtima‘iyyah. The implementation of these strategies has succeeded in gradually forming the character of students, although there were challenges of adaptation in the early stages. This study recommends strengthening the capacity of murabbi, balancing the motivation and sanction systems, and further research to develop a more holistic model of Islamic character education